Tiga Senyawa Oligostilbenoid dari Kulit Batang Dipterocarpus retusus Blume (Dipterocarpaceae) - Muhtadi Muhtadi; Euis Holisotan Hakim; Yana Maolana Syah; Lia Dewi Juliawaty; Sjamsul Arifin Achmad; Ikram M. Said; Jalifah Latip (Jurnal Matematika & Sains, 2005)
Three oligostilbenoids, (-)-Îµ-viniferin, (-)-Î±-viniferin and (-)-vaticanol A, together with two derivative coumarin compounds, scopoletin and (-)-bergenin, were isolated from acetone extracts of the tree bark of Dipterocarpus retusus Blume. The chemical structure of the isolates were established based on spectroscopic data, UV, IR, 1H-NMR, 13C-NMR, and by comparison with the related compounds. (-)-Îµ-Viniferin, (-)-Î±-viniferin and (-)-vaticanol A showed cytotoxic activity against murine leukaemia P-388 cells with their IC50 values were 7,8; 17,5 and 27,0 Âµg/mL, respectively.